Prevalence of premenstrual syndrome and its psychological effects among university students who participate and do not participate in resistance training - Eliane Aragão da Silva; Daniel Alvarez Pires (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT The study aimed to investigate the prevalence and effects of premenstrual syndrome (PMS) on the psychological factors of university students who do and do not participate in resistance training. The initial sample consisted of 81 participants, and the prevalence of PMS was 64.2%. Forty women diagnosed with PMS were divided into two groups: women who participated in (GP) and did not participate in (GNP) resistance training. The intergroup comparison showed significant differences (with higher scores in the GNP) in the items: difficulty concentrating, lack of energy, and feeling under pressure, and they reported a greater influence of the symptoms on their family relationships. It is concluded that women who participate in resistance training have reduced indicators of some psychological symptoms of PMS.